Rb4Li2TiOGe4O12: a novel high-performance titanyl germanate anode for Li-ion batteries. Issue 13 (15th March 2023) - Tang, Chuan; Chang, Siliang; Wu, Qian; Kang, Lei; Feng, Kai; Meng, Xianghe; Chu, Shengqi; Huang, Hongwei; Xia, Mingjun
Abstract : A polar polyanionic germanate Rb4 Li2 TiOGe4 O12 was proposed as a new high-performance anode for Li-ion batteries. It has balanced electrochemical properties with higher specific capacity and lower operating voltage, among the titanyl-based anodes. Abstract : The design of high-performance anode materials is the key to improving the performance of lithium-ion batteries. Here, a new high-performance titanyl germanate anode, Rb4 Li2 TiOGe4 O12 (RLTG), was investigated for lithium-ion storage properties for the first time. Thanks to the multi-electron reactions of Ti and Ge and the polyanion framework, RLTG exhibits a high discharge specific capacity of 786.2 mA h g −1 and decent capacity retention performance of 84%. In addition, RLTG shows a good rate capability in the range of 0.05–2.5 A g −1 . Furthermore, the discharge/charge behaviors were explored in depth by a cyclic voltammetry test, galvanostatic intermittent titration technique, X-ray absorption near-edge spectroscopy and electrochemical impedance spectroscopy, combined with first-principles calculations.